Cybernetic Drawing. A Unifying Language of Pask’s Cybernetics and Computer Art in Germany (diségno, 2018)
The essay provides an overview of relationships between the cybernetics with a special emphasis on the British cybernetician Gordon Andrew Speedie Pask and the computer art developed in Germany in the 1960s-70s with an introduction to the artists Frieder Nake and Georg Nees. In the 1960s, early computer artists, such as the Max Bense, Vera Molnar, Georg Nees, Frieder Nake and others, began to explore the relationships between art, design, science and the cybernetic principle of feedback. Their computer art investigated esthetics of computer languages for automated process of generative iterations away from the fixed states of pre-determined formalism. In the meantime, in the UK, Gordon Pask developed Conversation Theory, a formal model applied in his cybernetic ‘machines’. The networks and conversation diagrams that described CT represented possibilities of interaction between actors resulting in emergent forms of behavior. Both, the early computer art and Pask’s logic can are based on cybernetic foundations, as a unifying language. The fields’ concerns have expanded significantly and partly merged since then. The discussion still lies in the dichotomy between the urge for control and authorship over form and method of creation, and the approach of understanding form and its aesthetics as result of an activated dynamic systemic pre-programmed set of rules rather than states –all under the wings of a unifying language, namely cybernetics (read more).
Keywords: Cybernetics; Gordon Pask; Frieder Nake; Georg Nees; Computer Art; Germany